2019
DOI: 10.3389/fchem.2019.00125
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Biology Gateways to Mapping Location, Association, and Pathway Responsivity

Abstract: Here we discuss, how by applying chemical concepts to biological problems, methods have been developed to map spatiotemporal regulation of proteins and small-molecule modulation of proteome signaling responses. We outline why chemical-biology platforms are ideal for such purposes. We further discuss strengths and weaknesses of chemical-biology protocols, contrasting them against classical genetic and biochemical approaches. We make these evaluations based on three parameters: occupancy; functional information;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 162 publications
0
26
0
Order By: Relevance
“…Moreover, phenolate-based ligands are also appropriate to implement luminescence properties in order to design luminescent SMMs. [26][27] At room temperature and solid-state, both, 1 and 2 exhibit a broad ligand-based emission band located at with different emissions located at 615 and 550 nm, respectively (Fig. S12).…”
Section:  / Hzmentioning
confidence: 99%
“…Moreover, phenolate-based ligands are also appropriate to implement luminescence properties in order to design luminescent SMMs. [26][27] At room temperature and solid-state, both, 1 and 2 exhibit a broad ligand-based emission band located at with different emissions located at 615 and 550 nm, respectively (Fig. S12).…”
Section:  / Hzmentioning
confidence: 99%
“… 36 Coupling molecular probes with these zip codes can give insights into the environments in specific locales. 37 …”
Section: Methods Of Investigating Subcellular Localizationmentioning
confidence: 99%
“…Improving our understanding of protein signalling pathways triggered upon target-specific electrophilic modification by native electrophilic signalling molecules may pave a new pathway to targeting moonlighting functions of protein targets. [19,101,102] For example, in Cravatt's pioneering work of mapping LDE responders, he identified that sterile alpha motif and leucine zipper containing kinase (ZAK), one of the topranking hits of HNE, possesses a unique cysteine residue (C22) specific for 'sensing' HNE signals under oxidative stress, but is otherwise functionally silent in the basal state. [87,98,99] Additionally, Aye and co-workers have developed innovative proteomic platforms, such as Targetable Reactive Electrophiles and oXidants (T-REX) [99] and Genome-wide profiling of Reactive-Electrophile and -oXidant sensors (G-REX), [98][99][100] to profile and characterise protein responders that evolve a unique sensor cysteine primed for reactions with native LDE molecules, despite the presence of millimolars of GSH.…”
Section: Targeting Privileged Electrophile Sensors In Cell Signallingmentioning
confidence: 99%